1995
DOI: 10.1038/jcbfm.1995.102
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Glucose Transport and Metabolism in Cultured Neuronal Cells: Determination of the Rate-Limiting Step

Abstract: Summary: In brain and nerves the phosphorylation of glucose, rather than its transport, is generally considered the major rate-limiting step in metabolism. Since little is known regarding the kinetic coupling between these pro cesses in neuronal tissues, we investigated the transport and phosphorylation of [2-3H)glucose in two neuronal cell models: a stable neuroblastoma cell line (NCB20), and a primary culture of isolated rat dorsal root ganglia cells. When transport and phosphorylation were measured in serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 58 publications
1
20
0
Order By: Relevance
“…It is widely accepted that the major rate-limiting step in neuronal glucose metabolism is its phosphorylation by hexokinase, the first ATP-driven reaction of glycolysis (44). Insulin appears to upregulate hexokinase activity, localization, and expression, thus modulating glucose metabolism to meet the energy demands of sensory neurons (45).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that the major rate-limiting step in neuronal glucose metabolism is its phosphorylation by hexokinase, the first ATP-driven reaction of glycolysis (44). Insulin appears to upregulate hexokinase activity, localization, and expression, thus modulating glucose metabolism to meet the energy demands of sensory neurons (45).…”
Section: Discussionmentioning
confidence: 99%
“…Garfinkel et al derived this formula according to the data of Grossbard and Schimke (20) and assumed a random order ternary complex mechanism and assumed that G6P is a competitive inhibitor of ATP and a noncompetitive inhibitor of glucose. A sensitive and precise tracer technique allowed us to measure small amounts of enzyme activity at low substrate and high inhibitor concentrations (21). To use the glucose tracer data directly in the determination of the kinetic parameters, we modified the hexokinase rate law by dividing both sides of the equation by the concentration of glucose to correct for the specific activity of the tracer.…”
Section: Methodsmentioning
confidence: 99%
“…Inside the brain, a different transporter may be responsible for glucose transport across the cell membranes. However, several studies have suggested that the large surface area of brain cells may result in rapid equilibration inside the brain's aqueous phase leading to similar intra-and extracellular glucose concentrations (LundAndersen, 1979;Gjedde and Diemer, 1983;Holden et al, 1991;Gjedde, 1992;Silver and Erecitiska, 1994;Whitesell et a!., 1995).…”
Section: R Grue1ter Et Almentioning
confidence: 99%
“…Inside the brain, a different transporter may be responsible for glucose transport across the cell membranes. However, several studies have suggested that the large surface area of brain cells may result in rapid equilibration inside the brain's aqueous phase leading to similar intra-and extracellular glucose concentrations (LundAndersen, 1979;Gjedde and Diemer, 1983;Holden et al, 1991;Gjedde, 1992; Silver and Erecitiska, 1994;Whitesell et a!., 1995).Because the transporter isoform at the blood-brain barrier and that at the erythrocyte membrane are very similar, the kinetic constant for half-maximal transport, K,, should in principle be of similar magnitude. However, when reviewing the literature on animal brain glucose transport, a noticeable distribution of the measured brain K, was observed, ranging from 2 to 14 mM, as previously reviewed (Gjedde, 1992;Mason et a!., 1992).…”
mentioning
confidence: 99%